Analisis peramalan kebutuhan Alumunium Sulfat (Al2SO4)3 untuk meningkatkan kualitas produksi menggunakan metode Single Moving Average - Wardhani, Rachmasari Pramita; Lukman, Lukman; Sarungu, Selvia (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The quality of a product produced is a top priority for the company. The need for the use of chemicals for product quality in the company must also be taken into account so that it can be used efficiently, therefore in planning raw material requirements, a forecasting analysis of the needs of these secondary raw materials can be carried out. Based on the planning of the need for the use of these chemicals, the author conducted a study discussing the Forecasting of Aluminum Sulfate Al2(SO4)3 Needs in the company to improve production quality using the single moving average method. The study used qualitative and quantitative research methods, the study was aimed at seeing the application of the use of forecasting methods in companies and as a reference for learning the application of these methods for students. The author uses historical data on the use of Alum or Aluminum Sulfate in 2022 to May 2023 at one of the water treatment installations as a water purifier, with a movement value of n = 5,6,7,8,9. The results of the forecasting calculation obtained the lowest error rate in MSE and MAPE, namely at movement 5.